Wage bargaining and multinational firms in general equilibrium - Carsten Eckel; Hartmut Egger (Center for Economic Studies and ifo Institute (CESifo), 2006)
This paper studies the relationship between wage negotiations and the mode of foreign market penetration in a general equilibrium framework. We analyze the incentives of firms to set up a foreign production facility for improving their bargaining position vis-à-vis local unions. This renders the allocation of bargaining power among firms and unions a key determinant of the share of multinational enterprises and exporting firms. The economic mechanisms in this paper provide novel insights on how wages and unemployment rates adjust to economic integration. We distinguish between short-run effects for a given number of competitors and long-run effects after firm entry/exit. This allows us to identify possible globalization paths and to analyze their consequences for domestic labor markets.
Keywords: F12; F15; F16; F23; J51; 330